Seasonal abundance of zooplankton and growth performance of prawn and fish in ponds of Rajshahi - Siddique, MAB; Hussain, M Afzal; Hossain, MA; Alam, M Manjurul (University Journal of Zoology, Rajshahi University, 2012)
The present study was conducted on seasonal abundance of phytoplankton of prawn based carp polyculture system fishponds for a period of six months from September 2006 to February in the village Meherchandi of Boalia thana under Rajshahi district of Bangladesh. During the study period, it was found that water temperature varied from 16.59°C (T2) to 29.82 (T1), transparency 26.72 (T1) to 40.13cm (T2), pH 7.21 (T1) to 8.0 (T2) DO 2.13 (T2) to 3.6mg/l (T2), CO2 4.63 (T1) to 10.63mg/l (T2), NH3N 0.001 (T1) to 0.0197mg/l (T2) and total alkalinity fluctuated from 85.38 (T1) to 147.75mgl (T2). A total four groups of zooplankton were identified where 5 rotifera (38.41%) was dominant followed by 3 cladocera (31.49%), 2 copepoda (21.84%) and crustacean larvae (8.26%). It was also found that zooplankton showed abundance in February. The highest total average zooplankton (18390.79±2144.63 cells/l) was recorded in T1 than T2 which might be due to the effective uses by high stocking density of fishes. Zooplankton showed positive correlation with pH, DO, CO2 and alkalinity in T1. In case of T2, positive co-relationship was found with pH, DO, CO2 and NH3-N. The mean values of highest final weight of M. rosenbergii, H. molitrix and C. catla were 89.20±8.62g (T1), 682.70±44.20g (T2) and 428.00±4.50g (T1) respectively, highest survival rate was found 76.25±6.25% (T1) of prawn and highest total average yield was obtained 940.65±259.43 kg/ha in T2 due to high stocking densities of prawn. Key words: Zooplankton abundance; physico-chemical parameters; carp polyculture; growth performance DOI: http://dx.doi.org/10.3329/ujzru.v29i1.9459 UJZRU 2010; 29(1): 9-15